Efficacy of etravirine combined with darunavir or other ritonavir‐boosted protease inhibitors in HIV‐1‐infected patients: an observational study using pooled European cohort data1. Issue 5 (14th January 2015) - Vingerhoets, J; Calvez, V; Flandre, P; Marcelin, A‐G; Ceccherini‐Silberstein, F; Perno, C‐F; Mercedes Santoro, M; Bateson, R; Nelson, M; Cozzi‐Lepri, A; Grarup, J; Lundgren, J; et al.
<x xml:space="preserve">Abstract</x> Objectives This observational study in antiretroviral treatment‐experienced, HIV‐1‐infected adults explored the efficacy of etravirine plus darunavir/ritonavir (DRV group; n = 999) vs. etravirine plus an alternative boosted protease inhibitor (other PI group; n = 116) using pooled European cohort data. Methods Two international (EuroSIDA; EUResist Network) and five national (France, Italy, Spain, Switzerland and UK) cohorts provided data (collected in 2007–2012). Stratum‐adjusted (for confounding factors) Mantel–Haenszel differences in virological responses (viral load < 50 HIV‐1 RNA copies/mL) and odds ratios (ORs) with 95% confidence intervals (CIs) were derived. Results Baseline characteristics were balanced between groups except for previous use of antiretrovirals (≥ 10: 63% in the DRV group vs. 49% in the other PI group), including previous use of at least three PIs (64% vs. 53%, respectively) and mean number of PI resistance mutations (2.3 vs. 1.9, respectively). Week 24 responses were 73% vs. 75% (observed) and 49% vs. 43% (missing = failure), respectively. Week 48 responses were 75% vs. 73% and 32% vs. 30%, respectively. All 95% CIs around unadjusted and adjusted differences encompassed 0 (difference in responses) or 1 (ORs). While ORs by cohort indicated heterogeneity in response, for pooled data the difference between unadjusted and adjusted for cohort ORs was small. Conclusions These data do not indicate a difference in response between the DRV and other PI groups, although caution should be applied given the small size of the other PI group and the lack of randomization. This suggests that the efficacy and virology results from DUET can be extrapolated to a regimen of etravirine with a boosted PI other than darunavir/ritonavir.